Seismic reconnaissance survey in the Weddell Sea - Haugland, Kristen (Antarctic geoscience, 1982)
Paper No. 46
Keywords: NARE 1976/77; Sørishavet; Weddellhavet; ekspedisjoner; havbunnen; sedimentologi; seismologi

The Continental Margin of Queen Maud Land/Antarctica: Seismic Sequences, Structural Elements and Geological Development - Hinz, Karl; Krause, W (Geologisches Jahrbuch. Reihe E, Geophysik, 1982)
Keywords: Dronning Maud Land; geologi; kontinentalmargin; seismologi

A microearthquake survey of Bouvet Island, South Atlantic - Kristoffersen, Yngve; Bungum, Hilmar (Tectonophysics, 1982)
A microearthquake survey carried out during the 1978–1979 Norwegian Antarctic Research Expedition indicates that only minor seismic activity is associated with the Bouvet volcano.
Keywords: Bouvetøya; NARE 1978/79; geofysikk; seismologi; vulkaner